2019
DOI: 10.1186/s10086-019-1791-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preheating temperature, preheating time and their interaction on the sandwich structure formation and density profile of sandwich compressed wood

Abstract: Effects of preheating times (4, 8, and 12 min), preheating temperatures (75-210 °C, with 15 °C interval), and their interactions on structures and density profiles of sandwich compressed poplar wood (Populus × euramericana cv. 'Neva') were studied to achieve better control of the position(s) of compressed layer(s), with the aim of better utilization of the low-density wood resources. Our findings revealed that, as a result of preheating temperature elevation or preheating time extension, compressed layers move… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Therefore, the propagation of heat is faster in wood with lower density, lower thickness, and higher moisture content. The fast propagation of heat in the wood is an important factor in the densification process (Wu et al 2019). The internal parts quickly reach the appropriate temperatures so that the hydrogen bonds in the hemicelluloses, in the amorphous areas of the cellulose, and the lignin bonds achieve the appropriate stick-slap to reach visco-elastic deformation of the anatomical elements of the wood and thus adequate densification (Bao et al 2017).…”
Section: Discussion Thm Densification Process Evaluationmentioning
confidence: 99%
“…Therefore, the propagation of heat is faster in wood with lower density, lower thickness, and higher moisture content. The fast propagation of heat in the wood is an important factor in the densification process (Wu et al 2019). The internal parts quickly reach the appropriate temperatures so that the hydrogen bonds in the hemicelluloses, in the amorphous areas of the cellulose, and the lignin bonds achieve the appropriate stick-slap to reach visco-elastic deformation of the anatomical elements of the wood and thus adequate densification (Bao et al 2017).…”
Section: Discussion Thm Densification Process Evaluationmentioning
confidence: 99%
“…Surface hardness of compressed wood is generally significantly related with wood density [17,34]. Since sandwich compression can selectively densify wood surface or interior where required while the other areas/ zones in wood are almost intact [17][18][19][20][21][22][23], much less wood compressing percent is required to improve the surface hardness than traditional wood compression. In wood sandwich compression, density of wood interior beside the surface can be significantly increased based on the requirement, which can accordingly increase the surface hardness of the compressed wood.…”
Section: Hardness Of the Sandwich Compressed Timbersmentioning
confidence: 99%
“…Since the compressed layer(s) and thickness are both adjustable, this technology can minimize wood volume loss caused by the compression. So far, sandwich compression has demonstrated great successes for poplar wood [18][19][20][21][22][23], which is a typical plantation diffuse-porous hardwood. By adjusting the preheating temperature and time, compressed layer(s) position and thickness are both controllable.…”
Section: Introductionmentioning
confidence: 99%
“…By adjusting the parameters of preheating temperature and time, the compressed layer(s) in the direction of wood thickness can be softened and compressed, while the rest can be maintained. Our findings revealed that as results of preheating temperature elevation or preheating time extension, compressed layer(s) move gradually from wood surfaces to wood interior center, forming three types of sandwich compressed wood, namely surface compressed wood, internal compressed and central compressed wood [510]. It can also realize the directional control of the compression layer(s) position of sandwich compressed wood.…”
Section: Introductionmentioning
confidence: 99%
“…It can also realize the directional control of the compression layer(s) position of sandwich compressed wood. The yield stress gradients due to the gradient of hydrothermal distribution during compression are considered to be the cause of sandwich compressed wood formation [6,10]. After the wood was preheated for 0–600 s between the hot plates at 180°C, there was a significant linear correlation between the MC peak position in the high MC area of wood and the peak density of the compressed layer(s) in the sandwich compressed wood produced by preheating compression, and the moisture distribution on the wood thickness could be controlled by adjusting the preheating time, and finally the position and thickness of the compression layer(s) in the sandwich compressed wood can be controlled [8].…”
Section: Introductionmentioning
confidence: 99%